Stapedotomy Versus Hearing Aids in the Management of Conductive Hearing Loss Caused by Otosclerosis: A Prospective Comparative Study. Issue 7 (August 2022) - Molinier, Charles-Edouard; Gallois, Yohan; Deguine, Olivier; Iversenc, Gaetan; Vales, Olivier; Taoui, Soumia; Lepage, Benoit; Fraysse, Bernard; Marx, Mathieu
Abstract : Objective: To compare the outcomes of patients with unilateral otosclerosis treated consecutively by a hearing aid then stapedotomy. Study Design: Monocentric, nonrandomized, prospective, longitudinal, cohort study. Setting: Tertiary university hospital. Patients: Adult patients with a unilateral conductive hearing loss of at least 30 dB caused by otosclerosis. Interventions: Consecutive treatment by an external hearing aid followed by stapedotomy. Main Outcome Measures: Differences between hearing aids and stapedotomy in quality of life, pure-tone audiometry, binaural hearing, tinnitus severity, and patient satisfaction. Results: Twenty-two patients were included, of which 20 (91%) underwent stapedotomy. Stapedotomy demonstrated increased quality of life according to Glasgow Health Status Inventory scores versus hearing aids (+10.4 ± 9.4 [ p = 0.0001]). Stapedotomy versus hearing aids showed improved pure-tone averages (−11.1 ± 11.0 dB [ p = 0.002]) and air-bone gaps (−11.8 ± 10.7 dB [ p = 0.0006]). Stapedotomy was superior to hearing aids for speech-in-noise recognition in the reverse dichotic condition (−8.4 ± 26.9 dB [ p = 0.004]) and showed improved sound localization accuracy in root mean square error (−14.5 ± 24.5 degrees [ p = 0.02]). Stapedotomy, but not hearing aids, showed improved patient self-evaluated tinnitus after baseline adjustment according to the Tinnitus Handicap Inventory (−8.0 ± 13.4 [ p = 0.02]) and visual analog scale for tinnitus intensity (−28.7 ± 34.1 [ p = 0.006]). Overall, patients were more satisfied with surgery versus hearing aids. Conclusions: Stapedotomy remains more effective compared with hearing aids with greater improvements in quality of life, patient satisfaction, hearing outcomes, and self-evaluated tinnitus.